High refractive index hyperbranched polyvinylsulfides for planar one-dimensional all-polymer photonic crystals - Gazzo, Serena; Manfredi, Giovanni; Poetzsch, Robert; Wei, Qiang; Alloisio, Marina; Voit, Brigitte; Comoretto, Davide (Journal of Polymer Science Part B-Polymer Physics, 2016)
We report on the growth and characterization of one-dimensional (1D) planar all-polymer photonic crystals (PhC) with high dielectric contrast (Δn = 0.3) prepared by spin coating using hyperbranched polyvinylsulfide polymers (HB-PVS) as high refractive index material and cellulose acetate as low refractive index material. Solution processable HB-PVS show a near ultraviolet absorption inducing an increased refractive index in the visible-near infrared (n = 1.68, λ = 1000 nm). HBPVS:Cellulose Acetate Distributed Bragg Reflectors show a very clear fingerprint of the photonic band gap possessing the expected polarized dispersion properties as a function of the incidence angle. Moreover, engineered microcavities tuned on the weak fluorescence spectrum of the HB-PVS show directional fluorescence enhancement effects due to spectral redistribution of the emission oscillator strength. The combination of all these properties testifies the high optical quality of the obtained photonic structures thus indicating HB-PVS as an interesting material for the preparation of such PhC.
CRIS-Team Scopus Importer:2023-03-20
Keywords: distributed Bragg reflectors; hyperbranched polymer; microcavity; multilayer; photonic crystals; polyvinylsulfides